Immunogenicity of Pfizer mRNA COVID-19 Vaccination Followed by J&J Adenovirus COVID-19 Vaccination in Two Patients with Chronic Lymphocytic Leukemia - Zoe L. Lyski; Myung Sun Kim; David Xthona Lee; David Sampson; Hans-Peter Raué; Vikram Raghunathan; Debbie Ryan; Amanda E. Brunton; Mark K. Slifka; William B. Messer; Stephen E. Spurgeon (Case Reports in Hematology)
Individuals with chronic lymphocytic leukemia (CLL) have significant immune disfunction, often further disrupted by treatment. While currently available COVID-19 vaccinations are highly effective in immunocompetent individuals, they are often poorly immunogenic in CLL patients. It is important to understand the role a heterologous boost would have in patients who did not respond to the initial two-dose mRNA vaccine series. SARS-CoV-2 specific immune responses, including antibodies and memory B-cells, CD4 and CD8 T-cells were assessed prior to vaccination, as well as postinitial vaccination series and post-third dose in two subjects. One subject seroconverted, had RBD-specific memory B-cells and spike-specific CD4 T-cells while the other did not. Both subjects had a spike-specific CD8 T-cell response after the original mRNA vaccination series that was further boosted after the third dose or remained stable. The results of this study, however small, are especially promising to CLL individuals who did not seroconvert following the initial mRNA vaccination series.